Alliin enriched standardized fraction of Allium hookeri regulates the glucose homeostasis via upregulating hepatic glutathione pool - Barsha Deka; Pranamika Sarma; Prasenjit Manna; Jagat Chandra Borah; Narayan Chandra Talukdar (Elsevier, 2023)
Introduction: Allium hookeri is a source of organosulfur compounds including alliin which is an antihyperglycemic phytochemical. Purpose: This study tested the effect of methanolic extract (ME) of A. hookeri on glucose uptake and glutathione biosynthesis using sodium palmitate (0.75 mM) induced insulin resistant cultured hepatocytes. Method: The plant extract was prepared following standard protocol followed by bioactivity- guided fractionation. The plant extract and fractions were tested for glucose uptake assay, cellular glutathione level. Further, immunoblotting study was carried out to check the protein expression of the genes involved in glutathione biosynthesis and glucose metabolism. Results: Bioactivity-guided fractionation showed that the aqueous fraction from the methanolic A. hookeri extract (ME) was rich in alliin and the alliin-enriched standardized fraction (EFr) appeared to regulate glucose homeostasis as the cellular glutathione pool in the palmitate treated hepatocytes remained unaltered. Alteration in cellular glutathione level affects glucose homeostasis. We also observed that expressions of glutamate cysteine ligase (GCLC), glutathione reductase (GR), genes involved in hepatic glutathione biosynthesis were downregulated in palmitate and upregulated in EFr treated hepatocytes. GLUT2 protein expression was upregulated in the palmitate treated and downregulated in the EFr treated hepatocytes, but no change was observed in the protein expression of the gene glutathione synthase (GS). Conclusions: Our results show that EFr of A. hookeri leaves may be a potent botanical drug against type2 diabetes due to its role in the regulation of hepatic glutathione pool.